Plan de marketing para el posicionamiento de la empresa pública de movilidad de la mancomunidad de Cotopaxi. - Sarzosa Herrera, Edison Aurelio (2020)
The objective of this project was the creation of a marketing plan for the positioning of the Public Mobility Company of the Cotopaxi Commonwealth ("EPMC") so, the theoretical framework related to marketing strategies and the positioning of public organizations were analyzed, and the positioning of the entity as well as its competition was diagnosed too. Then, it was found that the "EPMC" is at a disadvantage concerning the Mobility Directorate of the Decentralized Autonomous Government ("GAD") of Latacunga canton. Subsequently, the descriptive exploratory research approach was used where 380 people participated in line with the population sample of drivers or owners of vehicles registered in Cotopaxi province. The main problem is the lack of positioning of the "EPMC" in the people from Cotopaxi, limiting the actions of the organización in favor of the community. The results show the company has the following main strengths: qualified professionals, reliable suppliers, liquidity funds, excellent and proper related service delivery processes; regarding weaknesses: the absence of a strategic and marketing plan, high-rivalry with its main competitor, inadequate facilities, dissatisfied customer service, unattractive corporate image; about opportunities: growing automotive business, access to technology to modernize its processes, policies to reduce the environmental impact that promotes the vehicle technical review service; finally, threats: strengthen competition in the market, country political instability, economic decline, and high-rivalry. Based on the analysis, marketing strategies aimed at increasing user uptake, renewing the business's corporate image, promoting its services through social networks, and building loyalty among its users were established. As a result, this project's execution requires a budget of USD 22,848.00 for each year, with USD 114,240.00 after five years. Additionally, the marketing ROI formula applied to the 2020 year was used to establish its feasibility where per each dollar that would be invested in the marketing plan, USD13,67 would return to the company